2017
DOI: 10.1055/s-0043-105077
|View full text |Cite
|
Sign up to set email alerts
|

National German Audit of Diagnosis, Treatment, and Teaching in Secondary Adrenal Insufficiency

Abstract: Great heterogeneity seems to exist regarding diagnosis, therapy, and teaching of patients with secondary adrenal insufficiency (SAI) across Germany resulting in different diagnosis and treatment strategies. The aim of the work was to present the first national audit on diagnosis, treatment, and patient teaching of SAI reflecting common clinical practice in Germany. A self-designed questionnaire was sent via e-mail to all members of the German Endocrine Society (approx. 120 centers). Returned questionnaires (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…73 % of the German endocrine centers hand out the emergency card of the German patients' self-help network (Netzwerk für Hypophysen-und Nebennierenerkrankungen e.V. ), whereas 16 % use emergency cards distributed from 4 different pharmaceutical companies, and 6 % use self-made emergency cards [35]. These different national cards reduce the recognition value among emergency personnel and might lead to disbelief and ignorance among emergency staff regarding the patient's underlying illness.…”
Section: Current Shortcomingsmentioning
confidence: 99%
See 4 more Smart Citations
“…73 % of the German endocrine centers hand out the emergency card of the German patients' self-help network (Netzwerk für Hypophysen-und Nebennierenerkrankungen e.V. ), whereas 16 % use emergency cards distributed from 4 different pharmaceutical companies, and 6 % use self-made emergency cards [35]. These different national cards reduce the recognition value among emergency personnel and might lead to disbelief and ignorance among emergency staff regarding the patient's underlying illness.…”
Section: Current Shortcomingsmentioning
confidence: 99%
“…10 % reported that they had never increased their glucocorticoid dose [18]. The German national audit regarding SAI patients revealed that only 61 % of the centers prescribe additional hydrocortisone tablets, only 59 % prescribed prednisone/ prednisolone suppositories, 65 % a 100 mg hydrocortisone ampoule, 2 % a 50 mg prednisolone ampoule, 4 % hydrocortisone suppositories, and 5 % betamethasone liquid [35]. Patients are not educated well enough for emergency situations.…”
Section: Current Shortcomingsmentioning
confidence: 99%
See 3 more Smart Citations